A New Look at Old Books: The Collection of the Nassau Public Library in the mid-19th Century - Ballance, Virginia C. (International Journal of Bahamian Studies, 2013)
Discovery of a hitherto unknown printed catalogue of the collection of the Public Library in Nassau, Bahamas published in 1862 has given library historians a glimpse at the type of books and periodicals available to residents of Nassau during the first decades after emancipation. An analysis of the library’s collection may help to understand the role the library played in the cultural and intellectual life of the Colony and whether it had any influence on the cultural values of 19th century Bahamian society.